Verb âClean Using Waterâ In Balinese - Bratayadnya, Putu Agus (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This paper discusses about verb clean activity using water in Balinese. Unlike Indonesian that are only have less variation words to clean human body like mandi and keramas. Balinese has some more variations to say specific meaning for clean using water. From this phenomenon, the verbs are interested to discuss particularly using theory of Natural Semantic Metalanguage by Anna Weirzbickaâs in her book entitled Semantics: Primes and Universal which was published by Oxford University in 1996.This paper was analyzed using Descriptive Qualitative Method and did both library and field research method. Library research had done by finding the verbs in Balinese books and articles. Afterwards field research did with observation with asking some Balinese speakers. Five words are found to clean a human body; Mambuh (For cleaning hair), Mesugi (face) etc. Meanwhile one word (ngumbah) is neutral??. It means the word can be used to describe in human body and non-human body.Then the last, there are two words in Balinese which were found to describe cleaning activity using water in Balinese to clean something or the activity which not to clean human body like nyusud and ngepel.